The energy of internal areas: a systemic approach in Taranta Peligna - Rossana Gaddi; Luciana Mastrolonardo (Techne)
If urban centres need integrated responses to today’s polycrisis, in internal territories where the demand is lower and the per-capita hectare is greater, the ecological transition can be triggered at a cultural, environmental and technological level with a climate-positive approach that distributes energy in a collaborative-community way so that the energy contribution is functional to a new socially-based development model. Alongside academic research on the marginal areas of Abruzzo, a non-binding agreement with the administration of Taranta Peligna, a municipality in the Maiella National Park with strong marginality, attempts to trace a path of growth and value enhancement of both material resources (wool and water) and immaterial ones to react to an ongoing depopulation process.